The Effect of Earnings Per Share (EPS) and Operating Cash Flow (OCF) on Company Value with Return on Equity (ROE) as an Intervening Variable in Banking Sector Companies Listed on the IDX in 2020 – 2024 - Salma Putri Azzahra; Dwi Urip Wardoyo (Dinasti Publisher, 2025)
This study aims to examine the influence of Earning Per Share (EPS) and Operating Cash Flow (OCF) on company value as measured by Price to Book Value (PBV) in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2024, with Return on Equity (ROE) as a mediating variable. The method used in this study is panel data regression analysis with a random effect model, which is analyzed using Eviews 12 software. The data used is the annual financial statements of 36 banking companies listed on the IDX, with a total of 180 observations. The results show that EPS has a negative effect on PBV, while OCF has a significant positive effect on company value. Although ROE had a significant effect on PBV, Sobel's test revealed that ROE did not significantly mediate the effect of EPS and OCF on company value. The classical assumption tests performed (normality, multicollinearity, and heteroscedasticity) showed that the data met the assumptions required for regression analysis. This research contributes to the understanding of the factors that affect corporate value in the Indonesian banking sector, by highlighting the importance of OCF in increasing corporate value and showing that ROE does not function effectively as a mediator in the relationship between EPS and OCF and corporate value. Further research is recommended to expand the scope by considering external factors that may influence more comprehensive outcomes.